Qualitative analysis of interspecific hybrids of oil palm for bunch components and fatty acid composition - Mandal, P.K.; Sujatha, G.; Kumar, T. Krishna (Journal of Plantation Crops, 2009)
Elaeis oleifera or the American oil palm produces more liquid oil due to higher unsaturated fatty acid content compared to the commercial species Elaeis guineensis. However, due to erratic and poor yield, E. oleifera is not cultivated commercially. Interspecific hybrids are having the potentiality of combining yield and quality in the oil. Seven interspecific crosses were made involving six E. guineensis and five E. oleifera palms. These were evaluated for their bunch component and oil quality in terms of fatty acid composition along with control E. guineensis tenera (D X P) hybrids and E. oleifera parental palms. Bunch component analysis showed intermediate values for bunch weight as well as bunch related parameters including proportion of parthenocarpic fruits. However, the oil/mesocarp and oil/bunch were lower than those of the parents. Fatty acid composition showed intermediate value between the two parental species for all the fatty acids. Wide variability in fatty acid composition was found in progenies of two specific interspecific crosses. No correlation was observed between any two fatty acids. Out of seven interspecific crosses, three were found to be on par with the better performing E. oleifera parental palms with respect to fatty acids. Since performance of each palm is different, individual interspecific hybrid palm was assessed based on total unsaturated fatty acids and oleic acid content and 20 superior palms were selected, which could be employed for further back crossing programme to combine the quality of palm oil and yield.